2022
DOI: 10.1021/acs.macromol.1c02155
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Indolenine–Squaraine Foldamers with a Preferred Helix Twist Sense and Their Chiroptical Absorption and Emission Properties

Abstract: A series of dicyanomethylene-substituted cisoid indolenine squaraine polymers (X n up to 65) bearing chiral side chains were prepared via Yamamoto homocoupling of the respective dibrominated monomers and subsequent fractionation by preparative gel permeation chromatography. In this series, the steric demand of the alkyl side chains and the position of the stereogenic center were systematically varied in order to create a different degree of structural perturbation. While S-3,7-dimethyloctanol as the starting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 120 publications
(208 reference statements)
0
14
0
Order By: Relevance
“…4d). 9 Interestingly, a strong lowenergy maximum around 850 nm appears in the CD spectrum that is barely visible in the linear absorption spectrum (Fig. 5).…”
Section: Steady-state Datamentioning
confidence: 94%
See 1 more Smart Citation
“…4d). 9 Interestingly, a strong lowenergy maximum around 850 nm appears in the CD spectrum that is barely visible in the linear absorption spectrum (Fig. 5).…”
Section: Steady-state Datamentioning
confidence: 94%
“…6 in ref. 9), where it is assumed to be in a pure zigzag random coil conformation. Finally, we note that the absorption spectrum can be tted equally well by assuming that the zigzag random coil and helix conformations are covalently connected, e.g., by considering a polymer made of 24 chromophores (instead of 16 considered so far), where the rst 19 are in a squeezed helix conformation and the remaining ve chromophores constitute the zigzag random coil fraction (Fig.…”
Section: Linear Absorption and Circular Dichroism Spectra And Reneme...mentioning
confidence: 99%
“…More recently, Selby et al reported four squaraine polymers carrying chiral branched alkyl pendants (Figure 9B), which were acquired by Yamamoto homocoupling reaction. [130] The steric demand and stereogenic center of the pendants were adjusted to afford structural perturbation. The polymers took a homohelical structure in some solvents.…”
Section: Wwwadvopticalmatdementioning
confidence: 99%
“…Reproduced with permission. [ 130 ] Copyright 2022, American Chemical Society. C) Illustration of the CPL‐active cellulose derivatives bearing pyrene‐based side chains.…”
Section: Preparation Of Polymer‐based Circularly Polarized Luminescen...mentioning
confidence: 99%
“…Chiral organic dyes are used in organic solar cells, as chiroptical switches, , molecular sensors, catalysts for photochemical reactions, photodetectors, or in organic light emitting diodes (OLEDs). , A plethora of chiral chromophores, such as merocyanines, BODIPYs, perylene diimides, phthalocyanines, porphyrins, , and metal complexes, , is known. Also, chiral squaraine dyes have been developed for the above-mentioned applications. These dyes possess outstanding optical properties, such as a narrow absorption band in the red to near-infrared spectral region, and high photochemical stability and fluorescence quantum yields . A strategy to further enhance the chiroptical properties of dyes is to use excitonically coupled axially chiral chromophore dimers. , Since the first description of the exciton coupling theory by Kasha, , exciton coupling effects have extensively been used to tune the optical properties of organic dye assemblies. A chromophore dimer represents the smallest and therefore simplest coupled system, which is best suited to investigate the influence of, for example, distance , and mutual orientation , of the two chromophores, or their chemical heterogeneity ,, and effects of vibronic coupling on the optical properties of the dimer .…”
Section: Introductionmentioning
confidence: 99%